The Relationship Between Midwife Performance and the Level of Maternal Statisfaction at the Puskesmas of Sarwodadi Kabupaten Pemalang - Uswatun Khasanah (Journal of Midwifery Science: Basic and Applied Research, 2020)
This research aimed to determine correlation between midwife performance and maternal sastisfaction in Sarwodadi Public Health Centre Pemalang Regency. The corresponding research design used descriptive correlative with cross sectional approach. Sample of research were maternal labor in Sarwodadi Public Health Centre Pemalang Regency as many as 32  people. The sampling technique used accidental sampling. The data collecting instrument used questionnaire. The result showed that 50% respondents said that good midwifes performance and 50% respondents said that it was lacking. There were 68,8% respondents were dissatisfied, but 31,3% respondents were  satisfied. There correlation between midwife performance and maternal sastisfaction in Sarwodadi Public Health Centre Pemalang Regency (ρ value: 0,008). Recommendations are given to health workers to improve the quality of delivery services and the provision of midwifery services by considering psychological aspects